Fluoride content in paediatric dentifrices commercialized in Brazil. Issue 1 (7th November 2022) - Valadas, Lídia Audrey Rocha; Sena, Nara Juliana Custódio; Júnior, Francisco Josimar Girão; Lotif, Mara Assef Leitão; Passos, Vanara Florêncio; Squassi, Aldo
Abstract: Objectives: The aim of this study is to determine the total, soluble and ionic fluoride (IF) concentration in toothpastes for children since there is a lack of information about this data. Methods: Fifteen different brands of toothpastes were purchased in different cities in Brazil. The total fluoride (TF), total soluble fluoride (TSF) and IF of two samples of each brand were determined (μg/g F). Results: The concentration of TF found in the fluoride toothpastes ranged from 324.4 to 1466.2 μg/g F, TSF ranged from 214.6 to 1424.1 μg/g F and IF ranged from 108.3 to 1320.1 μg/g F. TSF ranged between TF and IF. Most toothpastes were formulated with sodium fluoride (NaF), and only one with monofluorophosphate (MFP). The concentrations of TF were below the reported values. TSF and IF were below the TF concentration. Conclusions: The measured TF was less than that declared by the manufacturer in all the products. Most of the evaluated fluoride toothpastes commercialized in Brazil showed concentrations of TF below what was stated on the packaging, but with enough TSF to provide an anti‐caries effect.